Control of early HIV-1 infection associates with plasmacytoid dendritic cell-reactive opsonophagocytic IgG antibodies to HIV-1 p24. (28th November 2016) - Tjiam, M. Christian; Sariputra, Lucy; Armitage, Jesse D.; Taylor, James P.A.; Kelleher, Anthony D.; Tan, Dino B.A.; Lee, Silvia; Fernandez, Sonia; French, Martyn A.
Abstract : Objectives: We have previously demonstrated that HIV-1 p24-specific plasmacytoid dendritic cell-reactive opsonophagocytic antibody (PROAb) responses associate with control of chronic HIV infection. Here, we examined whether HIV-1 p24-specific PROAbs associate with control of early HIV infection and their relationship with HIV-1 p24-specific IgG subclasses. Methods: Plasma collected at 8 and 52 weeks following primary HIV-1 infection was obtained from antiretroviral therapy-naïve patients who were classified as 'good' (plasma HIV-1 RNA < 5000 copies/ml; n  = 17) or 'poor' (HIV-1 RNA > 50 000 copies/ml; n  = 15) controllers at week 52. HIV-1 p24-specific PROAb responses were assayed using a plasmacytoid dendritic cell line (Gen2.2), and HIV-1 p24-specific IgG3, IgG1 and IgG2 levels were assayed by ELISA. Results: HIV-1 p24-specific PROAb responses increased in 'good controllers' ( P  = 0.01) but remained unchanged in 'poor controllers' between weeks 8 and 52. Of the HIV-1 p24-specific IgG subclasses measured, only IgG1 increased over this time period in 'good controllers' alone ( P  = 0.003), which correlated with the increase in HIV-1 p24-specific PROAb responses ( r  = 0.83, P  < 0.0001). Depletion of IgG1 from IgG preparations of 'good controllers' resulted in the inhibition of HIV-1 p24-specific PROAb responses. In the total patient cohort, plasma HIV-1 RNA levels at week 52 correlated inversely with changes in HIV-1 p24-specific PROAb responses ( r  = −0.37, P  = 0.04) and IgG1 ( r  = −0.51, P  = 0.003) levels between weeks 8 and 52. Conclusion: Control of early HIV-1 infection was associated with an increase in HIV-1 p24-specific PROAb responses, which was mediated by HIV-1 p24-specific IgG1 antibodies. These findings provide further evidence that antibodies to HIV core proteins may contribute to control of HIV-1 infection. Abstract : Supplemental Digital Content is available in the text